Cytomegalovirus Diseases of the Gastrointestinal Tract in Immunocompetent Patients: A Narrative Review - Pai-Jui Yeh; Ren-Chin Wu; Chyi-Liang Chen; Cheng-Tang Chiu; Ming-Wei Lai; Chien-Chang Chen; Cheng-Hsun Chiu; Yu-Bin Pan; Wey-Ran Lin; Puo-Hsien Le (Viruses, 2024)
Cytomegalovirus (CMV) is a potential pathogen that causes gastrointestinal (GI) tract diseases regardless of host immunity. In contrast to immunocompromised individuals, immunocompetent patients lack a comprehensive overview of the gastrointestinal manifestations. This study aims to provide a comprehensive summary of the current evidence regarding presentations, diagnostics, management, risk assessment, and outcomes in immunocompetent patients with CMV GI disease. A thorough literature search of English publications up to April 2022 was conducted across electronic databases to identify relevant articles, with eligible case series selected for detailed analysis. The majority of immunocompetent patients affected by CMV GI disease are typically elderly, critically ill, or burdened with comorbidities that compromise immunity. Clinical presentations range from subtle symptoms to severe surgical conditions, including instances of mortality. Specific clinical presentations, blood test results, or endoscopic features are lacking, necessitating reliance on histopathological tests such as immunohistochemistry staining for diagnosis. While antiviral therapy may offer benefits in improving outcomes, careful individual assessment is warranted due to diverse comorbidities and potential side effects. Mortality rates vary considerably based on underlying medical conditions and therapeutic approaches. It is imperative for clinicians to maintain vigilance for CMV GI disease among high-risk groups, despite their baseline immunocompetence, in order to enhance clinical outcomes.